BIPOLAR DISORDER MANIC EPISODE WITH PSYCHOSIS : A CASE REPORT - Amariannisa, Hani; Hidayat, M. Fitrah (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Bipolar disorder (BD) is a psychiatric disorder that presents with manic and depressive episodes. The mood episodes appear as random and unpredictable episodes. The frequency and course of manic and depressive episodes may vary in each case and be determined by environmental factors as well as patient susceptibility.. A 25-year-old man, looks age appropriate, lacks self-care. He was taken to the emergency room because he was making noise about recommendations since 1 week before he was admitted to the hospital. 3 days before came to hospital was confused, easily emotional and had difficulty sleeping, talking to herself, having difficulty communicating, including being in a trance and starting to borrow and owe money to other people. Patients also see and hear sounds that other people do not hear. Further studies are needed for the evaluation of patients with bipolar disorder with psychosis and to acknowledge the treatment options with psychosocial educations as the support the treatment of bipolar disorder.